Optimization of 204 veterinary drug residues method and establishing their mass spectrum library. Issue 1 (1st January 2021) - Li, Xiaoqin; Fang, Zhijuan; He, Xinye; Zhang, Shuqin; Ding, Hongliu; Ye, Hu
ABSTRACT: A multi-class multi-residue analytical method was validated in this paper for simultaneously identifying 204 veterinary drugs in pork by UPLC-QTRAP MS/MS, including sulfonamides, quinolones, β-agonists, and nitroimidazoles. MRM-IDA-EPI mode of QTRAP was used to establish a secondary mass spectrum library of these 204 veterinary drugs, which could enhance the qualitative analysis of suspect substances. The separation of substances was performed on a C18 column, with a gradient elution of 0.1% formic acid solution in water and methanol. Electrospray ionization (ESI), fast polarity switching, and scheduled MRM mode were used to collect the characterization results. Factors that affected the recovery were delicately optimized, such as solvent proportion, formic acid content, and purification method. We finally determined the extracting method with formic acid-acetonitrile-water (0.1:90:10, v:v:v ) and purifying method with Cleanert LipoNo as a package for dispersive solid-phase extraction. Matrix effects on the quantitative results were also investigated. Some compounds had strong matrix inhibition or enhancement, and the matrix matching external standard method was used to quantify the compounds accurately. The correlation coefficient R 2 was over 0.99 within the calibration linearity range for the detected 204 veterinary drugs. The limit of quantification (LOQ) was 0.5 ~ 5 μg/kg. The recoveries ranged from 61.4% to 118.8% with RSDs of 3.1% to 19.2% ( n = 6).